KETERLIBATAN PEMANGKU KEPENTINGAN DALAM PELAPORAN KEBERLANJUTAN PADA PERUSAHAAN PERTAMBANGAN DAN ENERGI DI INDONESIA - Shekinah Viorensi Widyakusuma; Faisal Faisal (Diponegoro Journal of Accounting, 2022)
This research aims to find out how mining and energy companies in Indonesia engage with their stakeholders through the Stakeholder Engagement Strategy as well as the differences between the engagement strategies used by mining and energy companies to improve their sustainability reports through a stakeholder engagement matrix.The researcher uses a documentation technique method on Indonesian mining and energy sector that publishes a sustainability report in the Global Reporting Initiative (GRI). The final sample size for this research is 12 companies with a total of 12 reports that meet the sample selection criteria in 2017. The test uses the content analysis method.The results of the study show that by using a stakeholder information strategy, companies disclose their involvement with stakeholders at the first level, namely the information strategy by 43% of their total actions. Meanwhile at the second level, namely the response strategy by 42%, and finally the third level engagement strategy by 16%. The results of the stakeholder engagement matrix show that 6 out of 12 sample companies have disclosed higher levels of involvement and stakeholders. Meanwhile, there are 2 companies that are very lacking in disclosing their involvement and stakeholders.